2019
DOI: 10.1016/j.jor.2019.04.020
|View full text |Cite
|
Sign up to set email alerts
|

The trends in robotic-assisted knee arthroplasty: A statewide database study

Abstract: Recent technological advancements have led to the utilization of robotic-assisted knee arthroplasty (raKA) in the operating room. Methods: All patients who underwent knee arthroplasty from 2009 to 2013 in NYS SPARCS were reviewed. raKAs and non-raKAs were compared for utilization and institutional trends. Results: Robotic-assistance increased by 500%. 80% of raKAs were performed in teaching hospitals. The trend increase was greater in teaching hospitals. Blood transfusion rates differed between raKA and non-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…achieves the same or better technical outcomes, fewer studies have shown changes in clinical outcomes [6]. We aimed to evaluate for differences in 3 of the immediate postoperative outcomes between the 2 groups: pain scores on POD0, 1, and 2; discharge disposition (home vs SAR); and time to discharge.…”
Section: Discussionmentioning
confidence: 99%
“…achieves the same or better technical outcomes, fewer studies have shown changes in clinical outcomes [6]. We aimed to evaluate for differences in 3 of the immediate postoperative outcomes between the 2 groups: pain scores on POD0, 1, and 2; discharge disposition (home vs SAR); and time to discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Medical robots can assist in various tasks such as treatment of patients [ 34 ], surgery, and recognition of surgical activities. Robot-assisted surgery provides advantages like minimal invasiveness [ 53 ], better vision, and better instrument control [ 54 – 56 ], thereby allowing its application in difficult environmental conditions [ 34 ] and facilitating complex surgeries [ 57 ].…”
Section: Medical Tasksmentioning
confidence: 99%
“…The utilization of robots in the operating room is increasing across multiple surgical subspecialties. More specifically, robotic-assisted surgery for hip and knee arthroplasty has rapidly evolved in the last several years, now with nearly every major implant company developing or offering a robot [1][2][3]. In a statewide database, use of robotic total knee arthroplasty increased over 500% from 2009 to 2013 [1].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, robotic-assisted surgery for hip and knee arthroplasty has rapidly evolved in the last several years, now with nearly every major implant company developing or offering a robot [1][2][3]. In a statewide database, use of robotic total knee arthroplasty increased over 500% from 2009 to 2013 [1]. Since the original more primitive robotic systems utilized in hip and knee arthroplasty, several other robotic systems have been developed with more advanced and variable features.…”
Section: Introductionmentioning
confidence: 99%